In situ nanoparticle embedding for authentication of epoxy composites - Pansare, Amol V.; Khairkar, Shyam R.; Shedge, Amol A.; Chhatre, Shraddha Y.; Patil, Vishwanath R.; Nagarkar, Amit A. (Advanced Materials, 2018)
In situ reduction of chloroauric acid inside an amine-cured epoxy matrix leads to formation of gold nanoparticles which are embedded inside the part. This phenomenon is leveraged to design an authentication system for composites wherein the particles are embedded spatially and are invisible to the naked eye. Under UV light, the particles diffract light and create an easily visible path. The particles penetrate inside the part and create a permanent, cost-effective, tamper-proof code. The advantage of this technique is that this authentication system can be built in composite parts after fabrication of the composite structure. As very small amount (nanograms) of particles are present in the part, negligible change in the thermal characteristics of the parent matrix is observed. The particles can be embedded easily in carbon fiber as well as glass fiber reinforced epoxy structures.
Keywords: authentication; barcoding; composites; embedded nanoparticles; Epoxy

AgQDs employing black box synthetic strategy: photocatalytic and biological behavior - Pansare, Amol V.; Shedge, Amol A.; Chhatre, Shraddha Y.; Das, Debabrata; Murkute, Punam; Pansare, Shubham V.; Nagarkar, Amit A.; Patil, Vishwnath R.; Chakrabarti, S. (Journal of Luminescence, 2019)
This investigation relates FRET, photocatalytic and a biological study of AgQDs which found to be dependent on particle size and capping agent used. Surface of AgQDs was one of the most important factors that govern its activity. AgQDs with BSA binding was systematically studied by fluorescence quenching and electrostatic interaction. AgQDs mainly interacted to site II of BSA, binding distance r evaluated according to the FRET theory and was 4.6 nm for AgQDs, which suggested transfer of energy (non-radioactive) between surface modified AgQDs and biological molecule BSA. The photocatalytic activity of AgQDs for the appreciable degradation of erythrosine dye using Ultraviolet-B light was investigated. AgQDs showed specific antibacterial activity against E. coli bacterial stain. Quantum dots displayed a pronounced and specific activity causing > 50% growth of COLO-205 and MCF-7 human cancer Cells at concentrations < 10(-7 )M. Hence, present black box synthetic protocol of AgQDs could be life science application.
Keywords: AgQDs; Black box; COLO-205; Photocatalytic

Hydrophobic interpenetrating polyamide-PDMS membranes for desalination, pesticides removal and enhanced chlorine tolerance - Khairkar, Shyam R.; Pansare, V, Amol; Shedge, Amol A.; Chhatre, Shraddha Y.; Suresh, A. K.; Chakrabarti, Subhananda; Patil, Vishwanath R.; Nagarkar, Amit A. (Chemosphere, 2020)
Hydrophobic membranes for desalination and toxic organic pollutant removal have been fabricated using polyamide - PDMS (polydimethylsiloxane) chemistries in a one-step protocol. The curing of polyamide and PDMS are orthogonal and co-curing both networks imparts hydrophobicity to the thin film composite membranes. The membranes exhibit increased adsorption of pesticides from the feed water along with maintaining excellent salt rejection capability (97% NaCl rejection), thus giving the membranes a multifunctional character. Three toxic pesticides have been used in this study to demonstrate the viability of combining osmosis desalination technology with organic matter adsorption. The membranes also show excellent resistance to fouling by toxic pesticides (85% salt rejection vs 67% for commercial membranes in the presence of pesticides) and significantly improved chlorine tolerance (93.8% salt rejection vs 86.5% for commercial membranes after 20 h of exposure to sodium hypochlorite solution). (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: PDMS (Polydimethylsiloxane); Pesticide rejection; Salt rejection; Water purification membranes

Nanocomposite of functional silver metal containing curcumin biomolecule model systems: Protein BSA bioavailability - Shedge, Amol A.; Pansare, Shubham V.; Khairkar, Shyam R.; Chhatre, Shraddha Y.; Chakrabarti, S.; Nagarkar, Amit A.; Pansare, Amol V.; Patil, Vishwanath R. (Journal of Inorganic Biochemistry, 2020)
Curcumin, a constituent of Curcuma longa L-Zingiberaceae is used in traditional Indian and worldwide medicine and shows anticancer and antioxidant properties. Curcumin has numerous biological and pharmacological ac-tivities but due to its hydrophobic nature, the major drawback is poor absorption and rapid elimination, rendering curcumin with the tag of a poor biomaterial. Hence, there is a need to develop functional metal containing curcumin model systems (FMCCMS) as a metallo-biomolecule to enhance the bioavailability of curcumin. We designed the interaction of silver metal ion with curcumin to form curcumin-silver nanocomposite (CURC-AgNCP) via ultrasonic synthetic route. Formations of FMCCMS were characterized by spectroscopic techniques. The crystalline face-centered cubic pattern and particle size of the nanocomposite was evaluated using X-ray diffraction and high-resolution transmission electron microscopy. The bonding of silver metal to curcumin was confirmed by X-ray photon spectroscopy. Interaction of the nanocomposite with bovine serum albumin (BSA) protein was performed using excitation, emission, and circular dichroism spectroscopy. In binding interaction of BSA, the negative value of Delta S degrees (-358.04 J mol(-1) K-1) and Delta H degrees (-129.42 KJ mol(-1)) demonstrates the hydrophilic nature of the nanocomposite. The binding distance r evaluated according to the Forster resonance energy transfer theory and was 4.69 nm for CURC-AgNCP, which suggested non-radiative transfer of energy between CURC-AgNCP and BSA. The role of FMCCMS metallo-biomolecule CURC-AgNCP in medicine for cancer activity can have immense importance and hence we performed Sulphorhodamine B based in-vitro cytotoxicity assay on human breast cancer Michigan Cancer Foundation-7 cell line.
Keywords: Ag-based CURC biomaterials; Breast cancer; Metal in medicine; Metallobiomolecules; Nanocomposite

"Shape-coding'': morphology-based information system for polymers and composites - Pansare, V, Amol; Chhatre, Shraddha Y.; Khairkar, Shyam R.; Bell, Jeffrey G.; Barbezat, Michel; Chakrabarti, Subhananda; Nagarkar, Amit A. (ACS Applied Materials & Interfaces, 2020)
Fiber-reinforced composites have become the material of choice for aerospace structures because of their favorable strength-to-weight ratio. Given the increasing amounts of counterfeit composite parts showing up in the complex aerospace supply chain, it is absolutely vital to track a composite part throughout its lifecycle-from production to usage and to disposal. Existing barcoding methods are invasive, affect the structural properties of composites, and/or are vulnerable to tampering. We describe a universal method to store information in fiber-reinforced composites based on solid-state in situ reduction leading to embedded nanoparticles with controlled morphologies. This simple, cost-effective, mild, surfactant-free, and one-step protocol for the fabrication of embedded platinum nanostructures leads to morphology-based barcodes for polymeric composites. We also describe a coding methodology wherein a 1 x 1 cm code can represent 3.4 billion parts to 95 trillion parts, depending on the resolution required along with access to morphology-based chemical encryption systems.
Keywords: barcoding chemical encryption; epoxy composites; nanoparticle morphology control; solid-state synthesis

Deciphering the sensing of alpha-amyrin acetate with hs-DNA: a multipronged biological probe - Pansare, V. Amol; Shedge, Amol A.; Sonawale, Maryappa C.; Pansare, V. Shubham; Mahakal, Akshay D.; Khairkar, Shyam R.; Chhatre, Shraddha Y.; Kulal, Dnyaneshwar K.; Patil, Vishwanath R. (RSC Advances, 2022)
In this study, we focus on the biomimetic development of small molecules and their biological sensing with DNA. The binding of herring sperm deoxyribonucleic acid (hs-DNA) with naturally occurring bioactive small molecule alpha-amyrin acetate (alpha-AA), a biomimetic - isolated from the leaves of Ficus (F.) arnottiana is investigated. Collective information from various imaging, spectroscopic and biophysical experiments provides evidence that alpha-AA is a minor groove sensor of hs-DNA and preferentially binds to the A-T-rich regions. Interactions of different concentrations of small molecule alpha-AA with hsDNA were evaluated via various analytical techniques such as UV-Vis, circular dichroism (CD) and fluorescence emission spectroscopy. Fluorescence emission spectroscopy results suggest that alpha-AA decreases the emission level of hsDNA. DNA minor groove sensor Hoechst 33258 and intercalative sensor EB, melting transition analysis (T-M) and viscosity analysis clarified that alpha-AA binds to hs-DNA via a groove site. Biophysical chemistry and molecular docking studies show that hydrophobic interactions play a major role in this binding. The present research deals with a natural product biosynthesis-linked chemical-biology interface sensor as a biological probe for alpha-AA: hs-DNA.